The role of discourse in family policy reform: The case of Finland. (August 2018) - Nyby, Josefine; NygÅrd, Mikael; Autto, Janne; Kuisma, Mikko; Blum, Sonja
Since 2010 and the onset of the economic crisis, Finnish governments have pressed for structural reforms, including unpopular cuts to family benefits and services. This article analyses the government discourse used for legitimating some of these reforms: the cutbacks in child benefit and the restriction of full-time childcare. It also assesses whether this discourse bore the hallmarks of a neoliberal austerity discourse, which could suggest that the reforms were not just a matter of fiscal balancing but also a matter of neoliberal welfare state restructuring. We argue that the economic crisis was central in the powerful 'communicative' discourse used by the governments for legitimating unpopular cuts. Not only did it draw on ideas from an austerity discourse advocating financial sustainability, fiscal prudency and debt reduction, it was also impregnated with ideas from a neoliberal worldview questioning some of the main principles of the 'Nordic' family policy model.